On Generalized Localization of Fourier Inversion Associated with an Elliptic Operator for Distributions - Ravshan Ashurov; Almaz Butaev; Biswajeet Pradhan (Abstract and Applied Analysis)
We study the behavior of Fourier integrals summed by the symbols of elliptic operators and pointwise convergence of Fourier inversion. We consider generalized localization principle which in classical Lp spaces was investigated by Sjölin (1983), Carbery and Soria (1988, 1997) and Alimov (1993). Proceeding these studies, in this paper, we establish sharp conditions for generalized localization in the class of finitely supported distributions.